Layer-by-layer assembled magnetic molecularly imprinted nanoparticles for the highly specific recovery of luteolin from honeysuckle leaves. Issue 10 (28th April 2021) - Tian, Xuemeng; Gao, Ruixia; Wang, Yue; He, Yulian; Hussain, Sameer; Heinlein, Jake; Tian, Jiahao; Pfefferle, Lisa D.; Tang, Xiaoshuang; Tang, Yuhai
Abstract : Eco-friendly layer-by-layer assembled magnetic molecularly imprinted nanomaterials were designed for the specific recovery of luteolin from bio-waste honeysuckle leaves. Abstract : Nowadays, the recovery of added-value compounds by pre-treatment and extraction has become imperative in the recycling and transformation of bio-waste. Hence, to achieve efficient bio-waste recycling and avoid the drawbacks of solvent and time consumption in traditional pre-treatment, a green and facile method of efficient separation and enrichment of luteolin (LTL) from honeysuckle leaves has been developed via the green synthesis of novel magnetic molecularly imprinted polymers (Fe3 O4 -LTL-MIPs). Fe3 O4 -LTL-MIPs were prepared in aqueous solution using polyethyleneimine and dopamine as eco-friendly bifunctional monomers via layer-by-layer assembly onto the amino-modified Fe3 O4 carriers. The thin sandwich-biscuit-like imprinting layer in Fe3 O4 -LTL-MIPs provides sufficient binding sites with enhanced uniformity and accessibility for the template molecules, thus facilitating excellent recognition ability and rapid mass transfer. The obtained nanomaterials show homogeneous morphology, good crystallinity, satisfactory superparamagnetism, ultra-fast adsorption kinetics, high recognition ability, and excellent reusability. Moreover, Fe3 O4 -LTL-MIPs as solid-phase extraction adsorbents exhibit high efficiency for the separation and enrichment of LTL from the honeysuckle leaves combined with HPLC analyses. Therefore, the Fe3 O4 -LTL-MIPs could be potentially exploited as a feasible and efficient way to meet the goals of green chemistry for selective recycling and enriching target compounds from complicated bio-waste matrices.